기업교육을 위한 마이크로러닝 콘텐츠 설계 및 구현 - 정효정(Hyojung Jung) (디지털콘텐츠학회논문지, 2019)
마이크로 러닝에 대한 교육 현장에서의 기대와 관심이 높아지고 있음에도 불구하고, 설계 및 개발을 안내하는 체계적이고 통합적인 설계 원리에 대하여 제시하고 있는 연구는 아직 미비한 편이다. 마이크로 러닝을 성공적으로 설계하고 개발하기 위하여 구체적인 설계 전략에 대하여 구체화할 필요가 있다. 이러한 필요성에 의거하여 본 연구에서는 선행연구 및 관련 이론에 대한 고찰 및 실제 콘텐츠 개발을 통하여 실효성 있는 설계 원리를 제안하고자 하였다. 본 연구에서는 마이크로 러닝 콘텐츠 개발 시 고려해야 할 6가지의 설계 원리를 제안하였고, 해당 원리를 적용하여 콘텐츠를 개발하였다. 최종적으로 개발한 마이크로 러닝 콘텐츠에 대한 사용성 평가 및 콘텐츠에 대한 인식 조사를 통해 효과성을 검증하였다. Despite the growing expectations and interest in the field of microlearning, little research is available on the systematic and integrated design principles that guide design and development. In order to successfully design and develop microlearning, specific design strategies need to be specified. Based on this necessity, this study attempted to suggest effective design principles through consideration of previous studies and related theories and development of actual contents. In this study, we proposed six design principles to consider when developing micro learning contents, and developed the contents by applying the principles. Finally, the effectiveness was verified through the usability evaluation of the developed micro learning contents and the recognition of the contents. KCI Citation Count: 27